Outcomes of Surgical Treatment in Patients with Symptomatic Calcified Brain Cysts - Clinical Study - ADEEBUL HASSAN; FAISAL SHABBIR; MUHAMMAD NAUMAN SHAHID (Pakistan Journal of Medical & Health Sciences, 2025)
Background: While rare, calcified brain cysts have the potential to be associated with large neurological symptoms related to their size and location. In symptomatic cases surgery is required to relieve pressure effects and improve quality of life. It was the purpose of this study to determine the outcome of surgical treatment of symptomatic calcified brain cysts. Aim: The clinical outcomes and postoperative recovery of patients who undergo surgical excision of symptomatic calcified brain cysts at Aziz Fatimah Hospital, Faisalabad were evaluated. Methodology: In the Department of Neurosurgery of Aziz Fatimah Hospital Faisalabad from January 2024 to December 2024 a prospective clinical study was carried out. Eighteen patients with symptomatic calcified brain cyst were included. Surgical excision of the cyst was done in all patients. Symptoms prior to the surgery, intraoperative findings, postoperative complications and recovery status were recorded and analyzed. 1 month and 3 months follow up after the surgery was done. Results: Most common presenting symptoms were persistent headache (66.7%), seizures (38.9%) and focal neurological deficits (22.2%). Complete excision was accomplished in 15 of 18 patients (83.3%), while partial excision was performed in 3 because of the cyst location near eloquent brain areas. In 88.9% of patients, postoperative improvement was noted with significant reduction in symptoms. There were 2 complications (11.1%) in 2 patients, transient hemiparesis and wound infection. No mortality was reported. This was an average of 5.2 ± 1.4 days hospital stay. Conclusion: Symptomatic calcified brain cysts are safe and effective to surgically manage and result in marked clinical improvement in most patients. Timely treatment and early diagnosis ensure that there are no long term neurological sequelae.